2012
DOI: 10.1002/chin.201233103
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: Gold‐Catalyzed Oxidative Cyclizations of cis‐3‐En‐1‐ynes To Form Cyclopentenone Derivatives.

Abstract: Scheme 3. Deuterium-labeling experiments.Scheme 4. The reaction using diazocarbonyl.Scheme 5. The nature of CÀH insertion.Scheme 6. A plausible reaction mechanism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 9 publications
(23 reference statements)
0
5
0
Order By: Relevance
“…As a result, the venerable C–H insertions by Rh carbenes/carbenoids have not been realized with the gold counterpart. 22 In addition, its electrophilicity is evident in the observed chloride abstraction from the reaction solvent, 1,2-dichloroethane, under acidic conditions (eq 3). In comparison, similar chloride abstractions were observed with Rh carbenes/carbenoids flanked by two electron-withdrawing acyl groups.…”
Section: Intermolecular Oxidation Of Terminal Alkynes Followed By Intmentioning
confidence: 99%
See 2 more Smart Citations
“…As a result, the venerable C–H insertions by Rh carbenes/carbenoids have not been realized with the gold counterpart. 22 In addition, its electrophilicity is evident in the observed chloride abstraction from the reaction solvent, 1,2-dichloroethane, under acidic conditions (eq 3). In comparison, similar chloride abstractions were observed with Rh carbenes/carbenoids flanked by two electron-withdrawing acyl groups.…”
Section: Intermolecular Oxidation Of Terminal Alkynes Followed By Intmentioning
confidence: 99%
“…While other research groups have shown the α-oxo gold carbene generated via the intermolecular oxidation strategy could undergo cyclopropanation with tethered alkenes in special cases, , the carbene center appears to be highly electrophilic and behaves mostly as a carbocation. As a result, the venerable C–H insertions by Rh carbenes/carbenoids have not been realized with the gold counterpart . In addition, its electrophilicity is evident in the observed chloride abstraction from the reaction solvent, 1,2-dichloroethane, under acidic conditions (eq ).…”
Section: Intermolecular Oxidation Of Terminal Alkynes Followed By Int...mentioning
confidence: 99%
See 1 more Smart Citation
“…27 Unlike nitrones, these pyridine-N-oxides are reluctant to undergo [3 þ 2] dipolar cycloadditions with alkynes and can participate as outer-sphere oxidants on a Au-coordinated alkyne. This external oxygenation strategy was widely successful in OÀH/NÀH insertion, 28 1,2-H shift for the synthesis of R,β-unsaturated carbonyls, 29 CÀH insertion, 30 cyclopropanation, 31 and halide abstraction from solvents. 32 7.…”
Section: Intermolecular Alkyne Oxygenationmentioning
confidence: 99%
“…Experimental evidence supporting the involvement of α-oxo gold carbenes is still lacking, and their involvement has been refuted in a number of studies. , It is likely that the key N–O cleavage step may be concerted with a 1,2-H (or alkyl) shift (Schemes and A) or a S N 2′ attack . In addition, a [3,3]-sigmatropic shift , is possible in many cases (Scheme B), and the antarafacial [1,3]-sigmatropic shift for N–O cleavage has not been completely ruled out …”
Section: Involvement Of the Gold Carbenes In The Cleavage Of N–o Bond?mentioning
confidence: 99%